1982
DOI: 10.1002/chin.198224245
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: UNEXPECTED ANTIINFLAMMATORY ACTIVITY OF STRUCTURALLY RIGID COMPOUNDS DERIVED FROM ANTIHYPERTENSIVE 6‐ARYLPYRIDAZINONES. III. SYNTHESIS AND ACTIVITY OF 7‐FLUORO AND 5‐OXO‐5H‐INDENO(1,2‐C)PYRIDAZINES

Abstract: Bei der Reaktion von p‐Fluorbenzoylpropionsäure (I) mit Formaldehyd und Alkali erhält man neben der Fluorbenzoylbutensäure (II) das Fluorbenzoyl‐furanon (III), welches zum Fluor‐indanon (IV) cyclisiert werden kann.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Benzylation of 3-hydroxy-5 H -indeno[1,2- c ]pyridazin-5-one, synthesized according to the method reported by Cignarella et al., was achieved upon reaction with benzyl bromide in refluxing EtOH in the presence of K 2 CO 3 (Scheme ).
2
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzylation of 3-hydroxy-5 H -indeno[1,2- c ]pyridazin-5-one, synthesized according to the method reported by Cignarella et al., was achieved upon reaction with benzyl bromide in refluxing EtOH in the presence of K 2 CO 3 (Scheme ).
2
…”
Section: Resultsmentioning
confidence: 99%
“…3-(Benzyloxy)-5 H -indeno[1,2- c ]pyridazin-5-one (1h). To a stirred solution of 3-hydroxy-5 H -indeno[1,2- c ]pyridazin-5-one (0.396 g, 2 mmol), prepared according a reported procedure, in 20 mL of EtOH, were added K 2 CO 3 (0.276 g, 2 mmol) and excess of benzyl bromide (1.03 g, 6 mmol). The reaction mixture was refluxed for 30 min and, after cooling to rt, filtered through a Celite pad.…”
Section: Methodsmentioning
confidence: 99%
“…The pyridazinone derivatives exhibit antihypertensive activity by virtue of their vasorelaxant property. In 1980s, 6-arylpyridazinones were synthesized, and the compounds such as 7-fluoro and 5-keto-5H-indeno(1,2-c)pyridazines (8) (Cignarella et al, 1982) were found to be antihypertensive. Around the same time, many other pyridazinone derivatives were synthesized and evaluated for various pharmacodynamic properties.…”
Section: Antihypertensivementioning
confidence: 99%
“…5 The 3-(2H)-pyridazinone nucleus is found in drugs that act on the cardiovascular system [6][7][8][9][10] or inflammatory system (Figure 1). [11][12][13][14][15][16][17][18][19] Compounds possessing this nucleus have been shown to exhibit a diverse range of pharmaceutical properties such as anticancer, 20 nephrotropic, [21][22][23][24] analgesic, 12,13 antidepressant, 11 hypotensive, 8,25,26 antianemic, 27 antibacterial, 28 antiaggregative 29 and antifungal activities. 30 Pyridazine derivatives are also well-known compounds in agrochemical research.…”
Section: Introductionmentioning
confidence: 99%